High Value of Patriotism - Davronov ulugbek mirzadavlatovich; Yusupov arabboy baxodirjon ogli; Jorayev nodirbek usmonali ogli; Turdimatov jamshidbek xudobergan ogli (Zien Journals, 2022)
A concept that expresses people's love and devotion to their homeland, their kitchen. Patriotism has been common to all people, nations and peoples for centuries
Keywords: Patriotism History; world; school; homeland